Motivational climate of group exercise sessions in nursing homes - Alexia Charles; Fanny Buckinx; Alexandre Mouton; Jean-Yves Reginster; Olivier Bruyère (BMC, 2020)
Abstract Background Motivational climate in exercise group environments would have an impact on adherence, effort and enjoyment. We examined the motivational climate among nursing home residents who were involved in group exercise sessions. Methods This cross-sectional study was conducted in 10 nursing homes of Liège area that offer group exercise sessions. Sociodemographic data (age, sex, body mass index), cognitive status (by the Mini Mental State Examination) and independence in activities of daily living (by the Katz Scale) were retrieved in the medical records. The "Abbreviated-Perceived Motivational Climate in Exercise Questionnaire" was translated into French and then administered face to face with a clinical researcher. This is composed of 6 ego-involving climate items (corresponding to rivalry, comparison and favoritism) and 6 task-involving climate items (corresponding to valorization, individual efforts, self-improvement and cooperation). Each item is ranged on a 5-point Likert scale ranging from 1 (not at all focused on ego or task) to 5 (totally focused on ego or task). Each subscale has a total score expressed as an average. Results A total of 102 subjects of exercise group sessions were included (84.3 ± 7.7 years and 83 (81.4%) women). The mean score of task-involving and ego-evolving motivational climate was respectively 3.57 (SD = 0.67) and 1.52 (SD = 0.49), suggesting that the motivational climate was more focused on the task-involving climate than on ego-involving climate. Some items results were of particular interest: 55.9% of the respondents found that the instructor doesn't remark/reward when they try hard, 63.7% said that the instructor doesn't encourage mutual aid and 38.2% found that instructor doesn't encourage to do new exercises. Conclusions Participants tended to perceive motivational climate as more task-involving than ego-involving. The absence of individual positive feedback, new exercises and mutual aid were also highlighted.